Successful Treatment of Refractory Wart with a Topical Activated Vitamin D in a Renal Transplant Recipient - Luciano Moscarelli; Filomena Annunziata; Anduela Mjeshtri; Nunzia Paudice; Aris Tsalouchos; Maria Zanazzi; Elisabetta Bertoni (Case Reports in Transplantation)
Warts are benign proliferations of the skin and mucosa caused by infection with human papillomavirus. They are commonly treated with destructive modalities such as cryotherapy with liquid nitrogen, local injection of bleomycin, electrocoagulation, topical application of glutaraldehyde, and local and systemic interferon-β therapy. These treatment modalities often cause pain and sometimes scarring or pigmentation after treatment. We herein report a case with a right index finger wart, which was successfully treated with a topical activated vitamin D.